Experimental and Numerical Study on the Combustion Characteristics of a Laminar Non-Premixed Methane Jet Flame in Oxygen/Carbon Dioxide Coflow - Zhang, Fan; Li, Xing; Xie, Shengrong; Wang, Junxiong; Wang, Xiaohan (Frontiers in Energy Research, 2022)
The combustion characteristics of laminar non-premixed CH4 jet flame in an O2/CO2 coflows with different oxygen mole fractions were studied experimentally. The flame heights at different oxygen concentrations and fuel jet velocity were obtained. The experimental observation shows that the luminosity of the CH4 jet flame in O2/CO2 coflow is different from that of the flame in air stream. A two-dimensional numerical study of a laminar non-premixed CH4 jet flame in the O2/CO2 coflow with the O2 mole fraction of 0.35 was conducted to analyze the effects of CO2 dilution on the flame. The distribution of OH radicals in the flame was measured experimentally using planar laser-induced fluorescence (PLIF) to validate the computational method adopted in this work, and the computational and experimental results of the OH distributions showed good consistency at various fuel flow velocities. Three artificial species were created in the numerical experiment to analyze the effects of the chemical reactions, third-body collisions, and transport properties of CO2 on the height, width, and temperature distribution of the flame. The results showed that CO2 participation in chemical reactions exerts significant effects on the flame and that the influences of the third-body effects and transport properties of CO2 on the jet flame are unremarkable. The global reaction pathways and distributions of important species in the laminar non-premixed CH4 jet flame were analyzed in detail to determine the mechanisms of the effects of CO2 on flame height and temperature. The entire flame can be divided into two parts based on the oxidation process. The H, O, and OH concentrations and distributions in different parts of the flame were influenced by CO2 dilution, resulting in different flame heights and temperature distributions.